Totipotent Embryonic Stem Cells Arise in Ground-State Culture Conditions - Morgani, Sophie M.; Canham, Maurice A.; Nichols, Jennifer; Sharov, Alexei A.; Migueles, Rosa Portero; Ko, Minoru S.H.; Brickman, Joshua M. (Cell reports (Cambridge), 2013)
Embryonic stem cells (ESCs) are derived from mammalian embryos during the transition from totipotency, when individual blastomeres can make all lineages, to pluripotency, when they are competent to make only embryonic lineages. ESCs maintained with inhibitors of MEK and GSK3 (2i) are thought to represent an embryonically restricted ground state. However, we observed heterogeneous expression of the extraembryonic endoderm marker Hex in 2i-cultured embryos, suggesting that 2i blocked development prior to epiblast commitment. Similarly, 2i ESC cultures were heterogeneous and contained a Hex-positive fraction primed to differentiate into trophoblast and extraembryonic endoderm. Single Hex-positive ESCs coexpressed epiblast and extraembryonic genes and contributed to all lineages in chimeras. The cytokine LIF, necessary for ESC self-renewal, supported the expansion of this population but did not directly support Nanog-positive epiblast-like ESCs. Thus, 2i and LIF support a totipotent state comparable to early embryonic cells that coexpress embryonic and extraembryonic determinants. [Display omitted] •Embryos cultured in 2i are blocked before extraembryonic lineage segregation•ESCs cultured in 2i express extraembryonic markers heterogeneously•Single 2i ESCs differentiate into both embryonic and extraembryonic lineages•LIF promotes proliferation of extraembryonically primed ESC populations Embryonic stem cells (ESCs) are isolated from preimplantation embryos and can contribute to all tissues of the embryo, but not extraembryonic tissues (e.g., placenta). Therefore, they are considered pluripotent, not totipotent. Brickman and colleagues now show that single ESCs cultured in the presence of MEK and GSK3 inhibitors (2i) coexpress embryonic and extraembryonic markers and contribute to both embryonic and extraembryonic tissues (e.g., are totipotent). A role of the cytokine LIF in ESC self-renewal is to support this totipotent population.